Review: Effect of the combined application of edible coatings and osmotic dehydration on the performance of the process and the quality of pear cubes - Rodriguez Racca, Anabel (2021)
The objective of the present work was to evaluate the combined effect of the application of edible coatings (sodium alginate and low methoxyl pectin) and different osmotic dehydration conditions (sucrose solution: 40 and 60 °Brix, temperatures: 20 and 40 °C, and times: 1, 2, 4, 8 and 16 h) on pear cubes (water loss, solid gain, performance ratio, the total color differences, mechanical properties, phenolic content, and sensory analysis). The results indicated that samples coated with low methoxyl pectin and treated under 60°Brix for 16 h at both temperatures (20 and 40 °C) presented the best process performance. Statistical analysis showed that the application of the coatings resulted in greater firmness and stiffness of the pear cubes at the end of osmotic dehydration. Besides, alginate coating best preserved the phenolic content (31.4%) than uncoated (26.04%) and pectin-coated (20.77%) ones. However, total color differences were not improved with the use of edible coatings (alginate or pectin). In terms of quality, the samples coated with both hydrogels had good overall acceptability by the evaluators and good mechanical properties. However, further studies are required to decrease the difference in color and leaching of bioactive compounds in pear cubes due to the osmotic dehydration treatment. Resumen: El objetivo del presente trabajo fue evaluar el efecto combinado de la aplicación de recubrimientos comestibles (alginato de sodio y pectina baja en metoxilo) y diferentes condiciones de deshidratación osmótica (solución de sacarosa: 40 y 60 ° Brix, temperaturas: 20 y 40 ° C, y tiempos: 1, 2, 4, 8 y 16 h) en cubos de pera (pérdida de agua, ganancia de sólidos, relación de rendimiento, diferencias de color totales, propiedades mecánicas, contenido fenólico y análisis sensorial). Los resultados indicaron que las muestras recubiertas con pectina de bajo metoxilo y tratadas bajo 60 ° Brix durante 16 horas a ambas temperaturas (20 y 40 ° C) presentaron el mejor rendimiento del proceso. El análisis estadístico mostró que la aplicación de los recubrimientos resultó en una mayor firmeza y rigidez de los cubos de pera al final de la deshidratación osmótica. Además, el recubrimiento de alginato conservó mejor el contenido fenólico (31,4%) que los no recubiertos (26,04%) y recubiertos de pectina (20,77%). Sin embargo, las diferencias de color totales no mejoraron con el uso de revestimientos comestibles (alginato o pectina). En términos de calidad, las muestras recubiertas con ambos hidrogeles tuvieron una buena aceptabilidad general por parte de los evaluadores y buenas propiedades mecánicas. Sin embargo, se requieren más estudios para disminuir la diferencia de color y la lixiviación de compuestos bioactivos en cubos de pera debido al tratamiento de deshidratación osmótica.